2xX+17=3^5:3^2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{5}{4x}-\dfrac{3}{2}=\dfrac{3}{2}+\dfrac{x}{2}\\ \Leftrightarrow5-6x=6x+2x^2\\ \Leftrightarrow2x^2+12x-5=0\\ \Leftrightarrow\left[{}\begin{matrix}x=\dfrac{-6+\sqrt{46}}{2}\\x=\dfrac{-6-\sqrt{46}}{2}\end{matrix}\right.\)
(25-2X)^3:5-3^2=4^2
(25-2X)^0,6-9=16
(25-2X)^0,6=16+9=25
..............................
=>x=-94,37349667
(2x-15)5=(2x-15)3
=> 2x-15=0 hoặc 2x-15=1 (vì 05=03)
=> 2x=0+15 hoặc 2x=1+15
=> 2x=15 hoặc 2x=16
=> x=15:2 hoặc x=16:2
=> x=7,5 hoặc x=8
Vậy x = 7,5 hoặc x = 8
`1/2 xx x +3/2 =7`
`=> 1/2 xx x = 7-3/2`
`=> 1/2 xx x = 14/2 -3/2`
`=> 1/2 xx x = 11/2`
`=> x= 11/2 :1/2`
`=> x=11/2 xx2`
`=> x= 22/2`
`=>x=11`
Vậy `x=11`
__
`3/2 xx x -2/7 xx(x-7/2)=18`
`=> 3/2 xx x -2/7x + 1=18`
`=> (3/2 -2/7 )x+ 1 =18`
`=> 17/14 x=18-1`
`=> 17/14x=17`
`=>x=17:17/14`
`=> x=17 xx 14/17`
`=>x=14`
a) \(\dfrac{1}{2}\times x+\dfrac{3}{2}=7\)
\(\dfrac{1}{2}\times x=7-\dfrac{3}{2}\)
\(\dfrac{1}{2}\times x=\dfrac{11}{2}\)
\(x=\dfrac{11}{2}\div\dfrac{1}{2}\\ x=\dfrac{11}{2}\times2\\ x=\dfrac{22}{2}=11\)
b) \(\dfrac{3}{2}\times x-\dfrac{2}{7}\times\left(x-\dfrac{7}{2}\right)=18\)
\(\dfrac{3}{2}\times x-\left(\dfrac{2}{7}x-1\right)=18\)
\(\dfrac{3}{2}\times x-\dfrac{2}{7}x+1=18\)
\(\dfrac{3}{2}x-\dfrac{2}{7}x+1=18\)
\(\dfrac{17}{14}x+1=18\)
\(\dfrac{17}{14}x=18-1\)
\(\dfrac{17}{14}x=17\)
\(x=17\div\dfrac{17}{14}\)
\(x=17\times\dfrac{14}{17}\)
\(x=14\)
\(a)\) \(2x-5=21\)
\(\Leftrightarrow\) \(2x=21+5\)
\(\Leftrightarrow\) \(2x=26\)
\(\Leftrightarrow\) \(x=26:2\)
\(\Leftrightarrow\) \(=13\)
\(b)\) \(\frac{3}{4}+\frac{1}{4}x=\frac{5}{6}\)
\(\Leftrightarrow\) \(\frac{1}{4}x=\frac{5}{6}-\frac{3}{4}\)
\(\Leftrightarrow\) \(\frac{1}{4}x=\frac{1}{12}\)
\(\Leftrightarrow\) \(x=\frac{1}{3}\)
a) \(13\cdot\left(7-x\right)=26\)
\(\Rightarrow7-x=\dfrac{26}{13}\)
\(\Rightarrow7-x=2\)
\(\Rightarrow x=7-2\)
\(\Rightarrow x=5\)
b) \(\left(4x-18\right):3=2\)
\(\Rightarrow4x-18=2\cdot3\)
\(\Rightarrow4x-18=6\)
\(\Rightarrow4x=6+18\)
\(\Rightarrow4x=24\)
\(\Rightarrow x=24:4\)
\(\Rightarrow x=6\)
c) \(2\cdot x+98\cdot2022=98\cdot2023\)
\(\Rightarrow2\cdot x=98\cdot2023-98\cdot2022\)
\(\Rightarrow2\cdot x=98\cdot\left(2023-2022\right)\)
\(\Rightarrow2\cdot x=98\cdot1\)
\(\Rightarrow x=\dfrac{98}{2}\)
\(\Rightarrow x=49\)
d) \(\left(x+1\right)+\left(x+3\right)+\left(x+5\right)+...+\left(x+101\right)=?\)
Thiếu đề
a) \(13.\left(7-x\right)=26\)
\(7-x=26:13\)
\(7-x=2\)
\(x=7-2\)
\(x=5\)
b) \(\left(4x-18\right):3=2\)
\(4x-18=6\)
\(4x=6+18\)
\(4x=24\)
\(x=24:4\)
\(x=6\)
a/ => 4x2 - 4x + 1 + 4x2 + 4x + 1 = 16
=> 8x2 = 14
=> x2 = 14/8
=> x = \(\frac{\sqrt{7}}{2}\) hoặc x = \(-\frac{\sqrt{7}}{2}\)
b/ => 6x2 - (6x2 - 11x - 10) = 17
=> 6x2 - 6x2 + 11x + 10 = 17
=> 11x = 7
=> x = 7/11
c/ => 2x(x + 5) - x2 - 5x = 0
=> 2x(x + 5) - x(x + 5) = 0
=> (x + 5)(2x - x) = 0
=> x(x + 5) = 0
=> x = 0
hoặc x + 5 = 0 => x = -5
Vậy x = 0 ; x = -5
d/ \(x^2+\frac{1}{x^2}+2x+\frac{2}{x}=-3\)
đề là như vầy hả
\(2x+17=3^5:3^2\)
\(2x+17=3^3\)
\(2x+17=27\)
\(2x=10\)
\(x=5\)
TL:
2 . x + 17 = 35 : 32
2 . x + 17 = 35 - 2
2 . x + 17 = 33
2 . x + 17 = 27
2 . x = 27 - 17
2 . x = 10
x = 10 : 2
x = 5
- HT -